1973
DOI: 10.1103/physreva.8.3247
|View full text |Cite
|
Sign up to set email alerts
|

One-Phonon Spectral Function for Solid Helium

Abstract: Approximate numerical calculations are used in order to understand some of the differences in size and shape of secondary structure obtained in calculations of the one-phonon spectral function for solid helium which have been reported in the literature. It is seen that Horner's self-consistent treatment of the bubble diagram significantly increases the size of such structure over that obtained in perturbative calculations such as used by Glyde and co-workers. A computational procedure used by Horner in evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…23 '33-35 They have also been discussed by Leath and Watson, 36 Ruvalds,25 and McMahan and Beck,37 where some controversy has arisen as to the precise origin of the double-peak structure. Ruvalds 25 has proposed that the secondary peak structure in the one-phonon spectral function of anharmonic crystals could be produced by two-phonon bound states and resonances.…”
Section: Discussionmentioning
confidence: 92%
“…23 '33-35 They have also been discussed by Leath and Watson, 36 Ruvalds,25 and McMahan and Beck,37 where some controversy has arisen as to the precise origin of the double-peak structure. Ruvalds 25 has proposed that the secondary peak structure in the one-phonon spectral function of anharmonic crystals could be produced by two-phonon bound states and resonances.…”
Section: Discussionmentioning
confidence: 92%
“…This implies that even in crystals with a *For a review see, e.g., Ref. 38. moderate anharmonicity, close attention must be paid to the lineshape, which can have a multipeaked structure for a one-phonon response.…”
Section: Discussionmentioning
confidence: 99%
“…Although their calculations were for a non-linear chain only, Leath and Watson have speculated that the additional peak might exist in solid He. MacMahan and Beck [14], on the other hand, have suggested that the subsidiary zone-boundary peaks found by Horner arise from a computational technique alone. Glyde [15] speculates that subsidiary peaks have not so far been observed in the experiments because they may be masked by multiphonon scattering.…”
Section: Introductionmentioning
confidence: 99%